Ubiquitination in Scleroderma Fibrosis and Its Treatment - Long, Ying; Chen, Weilin; Du, Qian; Zuo, Xiaoxia; Zhu, Honglin (Frontiers in Immunology, 2018)
Scleroderma (systemic sclerosis, SSc) is a highly heterogeneous rheumatic disease, and uncontrolled fibrosis in visceral organs is the major cause of death in patients. The transforming growth factor-β (TGF-β) and WNT/β-catenin signalling pathways, along with signal transducer and activator of transcription 3 (STAT3), play crucial roles in this fibrotic process. Currently, no therapy is available that effectively arrests or reverses the progression of fibrosis in patients with SSc. Ubiquitination is an important post-translational modification that controls many critical cellular functions. Dysregulated ubiquitination events have been observed in patients with systemic lupus erythematosus, rheumatoid arthritis and fibrotic diseases. Inhibitors targeting the ubiquitination pathway have considerable potential for the treatment of rheumatic diseases. However, very few studies have examined the role and mechanism of ubiquitination in patients with SSc. In this review, we will summarize the molecular mechanisms of ubiquitination in patients with SSc and explore the potential targets for treatment.